2016
DOI: 10.1002/2016gl069917
|View full text |Cite
|
Sign up to set email alerts
|

Insights from a refined decomposition of cloud feedbacks

Abstract: Decomposing cloud feedback into components due to changes in several gross cloud properties provides valuable insights into its physical causes. Here we present a refined decomposition that separately considers changes in free tropospheric and low cloud properties, better connecting feedbacks to individual governing processes and avoiding ambiguities present in a commonly used decomposition. It reveals that three net cloud feedback components are robustly nonzero: positive feedbacks from increasing free tropos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
191
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 172 publications
(223 citation statements)
references
References 77 publications
11
191
2
Order By: Relevance
“…i) It provides a physical basis for interpreting the result that the positive feedbacks due to rising high clouds under climate change are not limited to the tropics, but also extend to extratropical latitudes (36,37). The potential for cloud feedbacks at extratropical latitudes due to the static stability/iris mechanism (6) could be explored in future research.…”
Section: Discussionmentioning
confidence: 99%
“…i) It provides a physical basis for interpreting the result that the positive feedbacks due to rising high clouds under climate change are not limited to the tropics, but also extend to extratropical latitudes (36,37). The potential for cloud feedbacks at extratropical latitudes due to the static stability/iris mechanism (6) could be explored in future research.…”
Section: Discussionmentioning
confidence: 99%
“…LCC feedback is a major component of the overall cloud feedback (Clement et al, 2009; Qu et al, 2014; Zelinka et al, 2016). Previous regression analyses have shown that SST exerts a prime control on local and regional mean LCC variations, with inversion strength, a proxy for lower troposphere stability, being the next most important factor (Brient & Schneider, 2016; Qu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Focusing only on the cloud feedback mechanisms, Zelinka et al (2012a) and others used this approach to isolate the role of each of the fundamental cloud variables that contribute to the cloud radiative response: cloud cover, cloud optical depth or water phase (liquid or ice), and cloud altitude (or cloud temperature). The shortwave (SW) cloud feedback is primarily driven by changes in cloud cover and cloud optical depth, whereas the longwave (LW) cloud feedback is driven by changes in cloud cover, cloud optical depth, and cloud vertical distribution (e.g., Klein and Jakob, 1999;Zelinka et al, 2012bZelinka et al, , 2013Zelinka et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%